Ammonia (Nh3) Excrete Production And Performance Of Broker Chickens With The Addition Of Turmeric Rhyme (Curcuma Longa) Flour To Drinking Water - Andi Akhmad Fadillah; Sri Purwanti; Wempie Pakiding (Yayasan Rahmatan Fiddunya Wal Akhirah, 2024)
Ammonia is a gas resulting from the decomposition of protein residues in broiler chicken excreta. Turmeric (Curcuma longa) is a tropical plant that has antibacterial properties from the curcumin content and essential oils found in its rhizomes. The aim of this research was to determine the levels of ammonia excreta and the performance of broiler chickens by adding turmeric rhizome flour to their drinking water. There were 32 broiler chickens used. The feed used is starter and finisher phase feed. There were four treatments with four replications, namely treatment K0 (control), K1 (drinking water + 0.5 g/L amoxitin), K2 (drinking water + 16 g/L turmeric rhizome flour), K3 (drinking water + 20 g/L turmeric rhizome flour). The data obtained were analyzed for variance using a completely randomized design. Turmeric flour was given for three consecutive days before carrying out weekly performance measurements at the same time interval for four weeks. The parameters observed were performance (drinking water consumption, feed consumption, body weight gain, feed conversion, and final body weight), as well as ammonia production of broiler chickens. The results showed that giving turmeric rhizome flour had no significant effect of p>0.05 on the performance and ammonia production of broiler chickens with the best performance and lowest ammonia production in treatment K2 (drinking water + 16 g/L turmeric rhizome flour), namely drinking water consumption (197 .54±7.58 mL/e/d), feed consumption (83.57±5.14 g/e/d), feed conversion (1.65±0.14), body weight gain (51.08± 5.61 g/e/d), final body weight (1229.75±107.07 g/e) and ammonia production (33.20±7.54 mM). It can be concluded that the addition of 16 g/L turmeric rhizome flour (K2) to drinking water tends to produce better performance and less ammonia production